Handwerk als immaterielles Kulturerbe - Seng, Eva- Maria (Mythos Handwerk. Zwischen Ideal und Alltag)

Feeless Micropayments and Their Impact on Business Models - Klein, M.; Kundisch, Dennis; Stummer, C. (Handbuch Digitalisierung)

Vom Geschäftsmodell zum Geschäftsprozess - Eine Systematische Literaturrecherche - Regniet, Julian

Sustainable Automotive Industry - The Impact of Financial Stimuli on Consumers’ Decision-Making and Purchasing Behavior An Empirical Analysis of the German Automobile Market - Borgelt, Martin

Killing the Restaurant Industry Softly? Eine deskriptive Analyse von Restaurantbewertungen vor und nach dem Eintritt von Lieferdienstplattformen - Piesik, Bartosz Marek

Einmal Pandemie, nie mehr Sharing Economy? Eine ökonometrische Analyse der Auswirkungen der Covid-19 Pandemie auf Sharing Eco-nomy Plattformen - Katrin, Wild

Online-Bewertungen im B2B-Marketing–Eine qualitative Untersuchung der Motive und Strategien im Bewertungsprozess von B2B-Online-Bewertungen - Meier zu Wickern, Joelle

Covid Changes Everything? Eine deskriptive Analyse des Online-Bewertungsverhaltens vor und während der Corona-Pandemie - Kaspar, Waldemar

Vom Bewertungssystem zur Produktplanung - Eine Taxonomie zu Bewertungssystemen aus Sicht der Produktplanung - Peters, Lukas

Experimente im Bereich der Online-Bewertungen - Ein systematischer Literaturüberblick - Linnig, Jakob Antonio

Der Einfluss von Online-Bewertungen auf die Kaufentscheidung - Literaturüberblick - Gertner, Anna

Erfolgsfaktoren von Crowdfunding-Plattformen - Amanzada, Ahmad Saki

Einmal Pandemie, nie mehr Sharing Economy? - Eine ökonometrische Analyse der Auswirkungen der Covid-19 Pandemie auf Sharing Economy Plattformen - Grote, Linda

Stiffness optimization and reliable design of a hip implant by using the potential of additive manufacturing processes - Risse, Lena; Woodcock, Steven Clifford; Brüggemann, Jan-Peter; Kullmer, Gunter; Richard, Hans Albert (BioMedical Engineering OnLine)
Abstract Background Due to the steadily increasing life expectancy of the population, the need for medical aids to maintain the previous quality of life is growing. The basis for independent mobility is a functional locomotor system. The hip joint can be so badly damaged by everyday wear or accelerated by illness that reconstruction by means of endoprostheses is necessary. Results In order to ensure a high quality of life for the patient after this procedure as well as a long service life of the prosthesis, a high-quality design is required, so that many different aspects have to be taken into account when developing prostheses. Long-term medical studies show that the service life and operational safety of a hip prosthesis by best possible adaptation of the stiffness to that of the bone can be increased. The use of additive manufacturing processes enables to specifically change the stiffness of implant structures. Conclusions Reduced implant stiffness leads to an increase in stress in the surrounding bone and thus to a reduction in bone resorption. Numerical methods are used to demonstrate this fact in the hip implant developed. The safety of use is nevertheless ensured by evaluating and taking into account the stresses that occur for critical load cases. These results are a promising basis to enable longer service life of prostheses in the future.
Keywords: Radiology; Nuclear Medicine and imaging; Biomedical Engineering; General Medicine; Biomaterials; Radiological and Ultrasound Technology

Methodenentwicklung zur numerischen Lebensdauerprognose von hyperelastischen Klebverbindungen infolge zyklischer Beanspruchung mittels bruchmechanischer Ansätze - Tews, Karina; Aubel, Tobias; Teutenberg, Dominik; Meschut, Gerson; Duffe, Tobias; Kullmer, Gunter (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Bewertung der Knochen-Schraube Verbindung im Auszugtest und unter physiologischer Belastung in der Finite Elemente Methode - Woodcock, Steven Clifford; Schramm, Britta; Kullmer, Gunter; Richard, Hans Albert

Global energy release rate of small penny-shaped cracks in hyperelastic materials under general stress conditions - Duffe, Tobias; Kullmer, Gunter; Tews, Karina; Aubel, Tobias; Meschut, Gerson (Theoretical and Applied Fracture Mechanics)

Fracture mechanical concept to predict crack nucleation in elastic adhesive joints - Duffe, Tobias; Tews, Karina; Kullmer, Gunter; Meschut, Gerson (ECF23, European Conference on Fracture 2022)

Numerische Lebensdauerprognose von hyperelastischen Klebverbindungen mit einem bruchmechanischen Ansatz - Duffe, Tobias; Tews, Karina; Aubel, Tobias; Meschut, Gerson; Kullmer, Gunter (Fachzeitschrift für Schweißen und verwandte Verfahren)

Privacy-Preserving Cryptography: Attribute-Based Signatures and Updatable Credentials - Eidens, Fabian